Gambaran Aktivitas Serum Glutamic Pyruvic Transaminase (SGPT) pada Petugas Batubara di Talang Duku Kabupaten Muaro Jambi - Aminahtun Latifah; Dewi Kurniasih; Muslina Muslina (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Dust generated from the coal production process is known to have various cytotoxic and carcinogenic contents. Prolonged exposure to coal dust can trigger health problems and affect the function of organs, one of which is the liver. Liver damage is characterized by increased activity of the enzyme Serum Glutamic Pyruvic Transaminase (SGPT), which is an indicator of liver function tests. Groups at risk of exposure to coal dust include people who are in the coal transport traffic area and the coal workers themselves. The study was conducted to describe the activity of Serum Glutamic Pyruvic Transaminase (SGPT) in coal workers at Talang Duku, Muaro Jambi. The research was conducted descriptively with a cross sectional approach. The research was conducted on 30 coal workers at Talang Duku, Muaro Jambi. The Automatic method is used to check SGPT activity using a Chemistry Analyzer. Based on the results of the study most of respondents had normal SGPT activities (73.33%), both in respondents with characteristics aged <40 years (46.67%), working period <5 years (36.66%) and field work division (60%). The results of examining SGPT activity in coal workers at Talang Duku, Muaro Jambi, showed that most of respondents had normal SGPT activity (73.33%) as well as respondents with spesific characteristics.